2023
DOI: 10.3390/gels9070573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Osteogenic Potential of Fucoidan Containing Chitosan Hydrogel in the Treatment of Periodontal Intra-Bony Defects—A Randomized Clinical Trial

Abstract: Periodontal diseases significantly impact about half of the global population, and their treatment often encompasses relieving symptoms as well as regenerating the destroyed tissues. Revolutionary research in the management of periodontal disease includes biomaterials, a boon to re-generative dentistry owing to their excellent biological properties: non-toxicity, anti-inflammatory, biocompatibility, biodegradability, and adhesion. This study aimed to fabricate an injectable fucoidan containing chitosan hydroge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…At three-and six-month evaluations, this study found that the therapy significantly reduced probing depth values and increased clinical attachment levels than the group treated with concentrated growth factor (CGF). After nine months, defect filling in the hydrogel group was also more elevated than in CGF cluster (47).…”
Section: Bone Regenerationmentioning
confidence: 89%
“…At three-and six-month evaluations, this study found that the therapy significantly reduced probing depth values and increased clinical attachment levels than the group treated with concentrated growth factor (CGF). After nine months, defect filling in the hydrogel group was also more elevated than in CGF cluster (47).…”
Section: Bone Regenerationmentioning
confidence: 89%
“…EPO-FK506-CS/β-GP/GA hydrogel could promote periodontal tissue regeneration. Eshwar et al (2023) investigated an alginate-chitosan hydrogel, and clinical randomized trials indicated that the hydrogel enhanced the clinical attachment levels and fostered human bone regeneration, thus augmenting its potential in the field of tissue engineering.…”
Section: Classification Of Polymer-based Hydrogelsmentioning
confidence: 99%
“…Researchers are exploring the use of advanced materials, such as composites, hydrogels [22][23][24][25], and bioactive materials [26], to further enhance the performance of scaffolds. These materials may incorporate growth factors, signaling molecules, or other bioactive agents to promote cell adhesion, proliferation, and differentiation [27][28][29].…”
Section: Mid-2010s-presentmentioning
confidence: 99%